2008
DOI: 10.1038/ng.174
|View full text |Cite
|
Sign up to set email alerts
|

Genomic surveys by methylation-sensitive SNP analysis identify sequence-dependent allele-specific DNA methylation

Abstract: Allele-specific DNA methylation (ASM) is a hallmark of imprinted genes, but ASM in the larger nonimprinted fraction of the genome is less well characterized. Using methylation-sensitive SNP analysis (MSNP), we surveyed the human genome at 50K and 250K resolution, identifying ASM as recurrent genotype call conversions from heterozygosity to homozygosity when genomic DNAs were predigested with the methylation-sensitive restriction enzyme HpaII. Using independent assays, we confirmed ASM at 16 SNP-tagged loci dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
353
3
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(375 citation statements)
references
References 21 publications
(21 reference statements)
16
353
3
1
Order By: Relevance
“…Although low power makes comparison difficult, the range of heritability within the top 5% of probes in the Boks and colleagues study (0.62-0.94) is similar to that found for the top 5% of probes for CBMCs in our study (0.48-0.94). Studies of allele-specific methylation (ASM) have also found evidence for a high heritability of DNA methylation at a subset of genomic loci, with proportions varying with the method of analysis and the tissue examined (Kerkel et al 2008;Boks et al 2009;Zhang et al 2009Zhang et al , 2010Meaburn et al 2010;Schalkwyk et al 2010;Shoemaker et al 2010;Gertz et al 2011). Surprisingly, we found little evidence for an effect of common environment on the overall DNA methylation profile at birth using variance component analysis.…”
Section: Discussioncontrasting
confidence: 52%
“…Although low power makes comparison difficult, the range of heritability within the top 5% of probes in the Boks and colleagues study (0.62-0.94) is similar to that found for the top 5% of probes for CBMCs in our study (0.48-0.94). Studies of allele-specific methylation (ASM) have also found evidence for a high heritability of DNA methylation at a subset of genomic loci, with proportions varying with the method of analysis and the tissue examined (Kerkel et al 2008;Boks et al 2009;Zhang et al 2009Zhang et al , 2010Meaburn et al 2010;Schalkwyk et al 2010;Shoemaker et al 2010;Gertz et al 2011). Surprisingly, we found little evidence for an effect of common environment on the overall DNA methylation profile at birth using variance component analysis.…”
Section: Discussioncontrasting
confidence: 52%
“…First, they can be confounded by ASM that is associated with genotype, but which may not have any regulatory effect. The amount of ASM typically associated with genotype is not well understood, but recent reports suggest it is significant (20). More importantly, because imprinted methylation is not necessarily associated with genotypic variation, these methods will be inherently blind to some portion of ASM.…”
mentioning
confidence: 99%
“…Studies of hereditary non-polyposis colorectal cancer (Lynch syndrome) suggest that germline genetic variation may affect epigenetic marks resulting in cancer predisposition 28,29 31 . Further epigenetic mechanisms that modulate gene expression include miRNAs and miRNA binding sites which can be directly affected by SNPs 32 , and tandem repeats that can impact gene expression e.g.…”
Section: Susceptibility Loci and The Regulation Of Gene Expression Thmentioning
confidence: 99%